Męczeństwo – chrześcijańska wyłączność? - Krzysztof Kościelniak (Polonia Sacra, 2012)
The main aim of this article is to show the principal acts of martyrdom that have been found in nearly all the world major religious traditions. Martyrdom as a phenomenon peculiar to monotheistic religions (Christianity, Judaism, Islam) has also analogies in Far East belief systems (e.g. Buddhism, Shinto, Hinduism, Sikhism). The phenomenon of suicide martyrdom – not only specific to Islamic religion – forms of fundamental values of self-sacrifice as a supreme ideal – a God (gods) – given opportunity – for salvation of the soul, as much as for redemption of society and state. The text presents the ideals and religious ideologies and convictions which refer to martyrs who sacrifice their life for the sake of great value principle. Martyr, one who voluntarily suffers death rather than deny his religion by words or deeds; such action is afforded special, institutionalized recognition in most major religions of the world.